Immunohistochemistry examination to reveal the pathogenesis of Oral Squamous Cell Carcinoma - Ilyas, Syafruddin (International Journal of Ecophysiology, 2023)
Oral mucosal cancer is a type of cancer that develops from the lining of the oral cavity (mucosa). The main risk factors are smoking and drinking alcohol. The pathogenesis of oral mucosal cancer involves various interrelated etiologies such as smoking and alcohol consumption, human papilloma virus (HPV), and patients who have undergone hemopoietic stem cell transplants (stem cell transplants). Meanwhile, it does not rule out the possibility of internal factors such as genetics. There are several types of oral mucosal cancer, but oral squamous cell carcinoma is the most common type of oral cancer and represents more than 90% of all head and neck cancers. Immunohistochemical examination of the Oral squamous cell carcinoma smear biopsy material which included examination of antibodies in the form of cytokeratin, CDT1, Ki-67, Geminin, Mcm2, Î³-H2A/ histone family member X and Aurora-A, BCL-2, VEGF, p53, p63, p,73, Prb, c-erbB2 or HER2/neu, upregulation of telomerase (human telomerase reverse transcriptase; hTERT), loss of heterozygosity (Chromosome loci 3p, 8p, 9p, 4q, 11q, 13q, 17p), High-risk Human papillomavirus 16/18 (HR-HPV16 and 18), p16, Overexpression of EGFR, c-jun, c-fos, surviving (BIRC5), MMP-9, MMP9, TGF-, COX-1, and-2, and amplification of Cyclins D and E. Thus, paving the way for appropriate therapy.